========================================================================
Subject: Recurrence Relation Problem
========================================================================
Here is the problem that I presented at the end of the lecture on 11/23:
Find the "explicit" solution of this recurrence relation:
a_n = 2a_(n-1) + 3a_(n-2)
with these initial conditions:
a0 = 4
a1 = 5
I suggested that you write out the first few terms of the sequence,
to see if you can spot the pattern, and then to apply the algorithm form
today's lecture.
I will post the answer at the end of the Thanksgiving break.